Lifetime of Bacterial Messenger Ribonucleic Acid - Moses, V. (1965)
Moses, V. (University of California, Berkeley), and M. Calvin. Lifetime of bacterial messenger ribonucleic acid. J. Bacteriol. 90:1205–1217. 1965.—When cells from a stationary culture of Escherichia coli were placed in fresh medium containing inducer for β-galactosidase, growth, as represented by increase in turbidity and by total protein synthesis, started within 30 sec. By contrast, β-galactosidase synthesis was greatly delayed compared with induction during exponential growth. Two other inducible enzymes (d-serine deaminase and l-tryptophanase) and one repressible enzyme (alkaline phosphatase) showed similar lags. The lags were not due to catabolite repression. They could not be reduced by pretreatment of the culture with inducer, or by supplementing the fresh medium with amino acids or nucleotides. The lag was also demonstrated by an i(−) mutant constitutive for β-galactosidase synthesis. An inhibitor of ribonucleic acid (RNA) synthesis, 6-azauracil, preferentially inhibited β-galactosidase synthesis compared with growth in both inducible and constitutive strains. Puromycin, an inhibitor of protein synthesis, acted as an inhibitor at additional sites during the induction of β-galactosidase synthesis. No inhibition of the reactions proceeding during the first 20 sec of induction was observed, but puromycin seemed to prevent the accumulation of messenger RNA during the period between 20 sec and the first appearance of enzyme activity after 3 min. It is suggested that these observations, together with many reports in the literature that inducible enzyme synthesis is more sensitive than total growth to some inhibitors and adverse growth conditions, can be explained by supposing that messenger RNA for normally inducible enzymes is biologically more labile than that for some normally constitutive proteins. The possible implications of this hypothesis for the achievement of cell differentiation by genetic regulation of enzyme synthesis are briefly discussed.